2019
DOI: 10.1186/s12885-019-6104-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of immediate oncoplastic surgery and adjuvant radiotherapy in breast cancer patients

Abstract: Background Oncoplastic surgery techniques lead to a rearrangement of the breast tissue and impede target definition during adjuvant radiotherapy (RT). The aim of this study was to assess local control rates after immediate oncoplastic surgery and adjuvant RT. Methods This study comprises 965 patients who underwent breast-conserving therapy and adjuvant RT between 01/2000 and 12/2005. 288 patients received immediate oncoplastic surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…This was despite the propensity of OPM to be performed in younger patients with more advanced tumors, a characteristic shared in our study as well. Similarly, a recent retrospective study of 965 patients by Borm et al showed that while there was a trend to reduced boost utilization in patients with OPM in comparison to non-OPM patients, however overall rates were still high (94.2% vs. 91% p = 0.06) [8]. Furthermore, there were no signi cant differences in IBTR between OPM and non-OPM patients, supporting similar oncologic outcomes with adoption of OPM.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This was despite the propensity of OPM to be performed in younger patients with more advanced tumors, a characteristic shared in our study as well. Similarly, a recent retrospective study of 965 patients by Borm et al showed that while there was a trend to reduced boost utilization in patients with OPM in comparison to non-OPM patients, however overall rates were still high (94.2% vs. 91% p = 0.06) [8]. Furthermore, there were no signi cant differences in IBTR between OPM and non-OPM patients, supporting similar oncologic outcomes with adoption of OPM.…”
Section: Discussionmentioning
confidence: 83%
“…We also found no signi cant difference in delays to adjuvant radiotherapy. Any potential differences in incidence of IBTR could not be estimated due to the relatively short follow-up times and very few IBTR events, which were limitations also noted in previous studies [8,11,14,15,17,18]. Finally, we evaluated the relationship between the ratio of post-operative seroma volume to tumor size and reception of BRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no long-term differences in recurrence rates and survival between BCS and OPS have been reported 13,19,22,[43][44][45] , current evidence regarding the impact of OPS on the re-excision rate is limited because the data are from single-centre studies with relatively few patients undergoing OPS (ranging from 31 to 1177), and in most studies the methodology was weak 11,13,44,[46][47][48] . The present results are in line with a meta-analysis 19 from 2018 that found a significantly lower risk of re-excision in patients who underwent OPS compared with those who had BCS (relative risk 0⋅66, 95 per cent c.i.…”
Section: Discussionmentioning
confidence: 99%